2004
DOI: 10.1227/01.neu.0000129546.38675.1b
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Clinically Distinct New Subtype of Grade II Astrocytomas in Patients with Long-term Epilepsy

Abstract: Differences between astrocytomas with a very long seizure history and those with a very short seizure history do exist. Significant factors for prognosis were age at surgery and presence of postoperative tumor residue but not the presence of epilepsy per se. A new subtype of astrocytomas, provisionally called isomorphic LEA astrocytoma, has putatively been identified with significantly better survival and lower recurrence rate. The negative prognostic factor of a gemistocytic differentiation pattern in diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 18 publications
0
33
1
3
Order By: Relevance
“…8,12 Some authors have suggested that this phenomenon is related to different tumor histopathological characteristics. 16 However, this phenomenon may reflect a selection bias, because chronic epilepsy lasting for years without significant disease progression is de facto evidence of a slowly growing benign lesion. Patient age is a more reliable prognostic factor in neurooncology.…”
Section: Discussionmentioning
confidence: 99%
“…8,12 Some authors have suggested that this phenomenon is related to different tumor histopathological characteristics. 16 However, this phenomenon may reflect a selection bias, because chronic epilepsy lasting for years without significant disease progression is de facto evidence of a slowly growing benign lesion. Patient age is a more reliable prognostic factor in neurooncology.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a patient died of relentless recurrence and malignant transformation of low-grade ganglioglioma after intended subtotal resection for protection of memory function. Although it has been proposed that brain tumors presenting with chronic epilepsy are biologically indolent, 4,15 to the best of our knowledge, the prognosis cannot yet be predicted on a patient basis, and total tumor removal has an important meaning in the oncological perspective.…”
Section: 10mentioning
confidence: 99%
“…Following resection of the tumour, 82% of the group of 60 patients studied were seizure-free after one year. A similar group, consisting typically of low grade gliomas, has been studied more recently [124] and characterized by a low cellularity, lack of mitoses and the absence of certain protein expression, such as the microtubule-associated protein (MAP2) which is critical in neurogenesis. The protein stabilizes microtubules that are enriched in dendrites, implicating a role in stabilizing dendritic shape during neuronal development.…”
Section: Surgerymentioning
confidence: 99%